1980
DOI: 10.1128/aem.39.1.210-218.1980
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ozone Inactivation of Bacteriophage f2

Abstract: The inactivation kinetics of bacteriophage f2 were studied by using ozone under controlled laboratory conditions. The phage were rapidly inactivated during the first 5 s of the reaction by 5 and 7 logs at ozone concentrations of 0.09 and 0.8 mg/liter, respectively. During the next 10 min, the phage were further inactivated at a slower rate in both treatments. The [ 3 H]uridine-labeled f2 phage and its ribonucleic acid (RNA) were examined to elucidate the mechanism of ozone inactivation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(44 citation statements)
references
References 21 publications
(11 reference statements)
0
42
0
1
Order By: Relevance
“…It has been used for disinfection of drinking water in Europe since 1906 (Rice et al, 1981) and has also been installed in some sewage treatment plants (Oh et al, 2007;Rakness et al, 1993). The disinfecting ability of ozone treatment has been shown to be efficient for bacteria and parasites in clean water (Kim et al, 1999;Peeters et al, 1989), and this treatment also has been shown to reduce the concentrations of enteric viruses and bacteriophages (Burleson et al, 1975;Kim et al, 1980). However, the ability of ozonation to inactivate pathogens in wastewater might be hampered due to the high contents of organic materials in sewage (Burleson et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…It has been used for disinfection of drinking water in Europe since 1906 (Rice et al, 1981) and has also been installed in some sewage treatment plants (Oh et al, 2007;Rakness et al, 1993). The disinfecting ability of ozone treatment has been shown to be efficient for bacteria and parasites in clean water (Kim et al, 1999;Peeters et al, 1989), and this treatment also has been shown to reduce the concentrations of enteric viruses and bacteriophages (Burleson et al, 1975;Kim et al, 1980). However, the ability of ozonation to inactivate pathogens in wastewater might be hampered due to the high contents of organic materials in sewage (Burleson et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have long sought to provide mechanistic descriptions of virus inactivation during drinking water disinfection [1]. In the 1960-1980s, researchers employed scintillation spectroscopy and electron microscopy techniques to detect modifications in viral genomes and proteins and typically reported one of two conclusions: 1) inactivation is the result of damage to the virus proteins or 2) inactivation is the result of damage to the genome [2][3][4][5][6]. Although these early studies investigated the molecular mechanisms as much as technologically possible, more recent research has focused less on elucidating mechanisms and more on comparing inactivation kinetics with various virus strains, disinfectants, and water chemistries [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The main inactivation mechanism was instead found to be related to genome damage. In contrast, Kim et al (20) reported extensive ozone damage to the capsid of bacteriophage f2; these researchers surmised that the breakup of capsid proteins led to a loss of binding ability and subsequent genome delivery for this virus, while genome damage was viewed as a minor secondary inactivation mechanism. In addition, differences in inactivation mechanisms may also result from the applied disinfectant doses.…”
mentioning
confidence: 96%